2019
DOI: 10.3390/atmos10080450
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Atmospheric Waves in the Earth Lower Ionosphere by Means of the Method of the Creation of the Artificial Periodic Irregularities of the Ionospheric Plasma

Abstract: We present results of the studies of internal gravity waves based on altitude-time dependences of the temperature and the density of the neutral component and the velocity of the vertical plasma motion at altitudes of the lower ionosphere (60–130 km). The vertical plasma velocity, which in the specified altitude range is equal to the velocity of the neutral component, the temperature, and the density of the neutral atmosphere are determined by the method of the resonant scattering of radio waves by artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Horizontal wavelengths for these waves are in the range of 115 km< λ p < 161 km. This is consistent with the results known from the scientific literature (Fritts et al , 2014;Bakhmetieva et al , 2019), which emphasize that gravity waves with periods as short as 10 minutes (i.e. Ω < 0.24, or ω < 0.01s −1 ) can carry significant momentum flux vertically.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Horizontal wavelengths for these waves are in the range of 115 km< λ p < 161 km. This is consistent with the results known from the scientific literature (Fritts et al , 2014;Bakhmetieva et al , 2019), which emphasize that gravity waves with periods as short as 10 minutes (i.e. Ω < 0.24, or ω < 0.01s −1 ) can carry significant momentum flux vertically.…”
Section: Discussionsupporting
confidence: 92%
“…These waves have lower vertical phase velocities than high-frequency gravity waves with ω ≈ ω BV which travel faster through the ionospheric D layer towards the lower thermosphere. The reflection coefficient is the smallest for the gravity waves with the frequencies ω < 0.0087s −1 , horizontal phase velocities 159m/s < v h < 222m/s, and horizontal wavelengths 115 km< λ p <161 km, which is in accordance with the results known in the scientific literature (Lizunov and Hayakawa , 2004;Fritts et al , 2014;Bakhmetieva et al , 2019). These waves can generate the middle-scale TIDs and cause temperature rise in the lower ionosphere.…”
Section: Discussionsupporting
confidence: 89%
“…Our long-term studies of the ionosphere by the API technique have shown that the relaxation time of the scattered signal fluctuates in height and in time [23,32,39,41]. Altitude profiles of the relaxation time τ(h) for 30 min of measurements are shown in Figure 2c.…”
Section: Data Processingmentioning
confidence: 93%
“…The atmospheric temperature and density are determined from the API relaxation time, which is inversely proportional to the ambipolar diffusion coefficient. Many results of studying the altitude-temporal variations of temperature and density in different geo-and helio-physical conditions are presented in Reference [23][24][25][26][27][28].…”
Section: Experimental Backgroundmentioning
confidence: 99%